Introduction to Lattices and Order - Davey, B. A. / Priestley, H. A. (New Delhi Cambridge University Press, 2009)
This new edition of Introduction to Lattices and Order presents a radical reorganization and updating, though its primary aim is unchanged. The explosive development of theoretical computer science in recent years has, in particular, influenced the books
Mathematics
Keywords: Lattices and Order